Analyses and design of steep slope with GeoBarrier System (GBS) under heavy rainfall - Rahardjo, Harianto (2021)
A GeoBarrier system (GBS) is a combination system of reinforced soil walls to stabilize near-vertical cut slopes and capillary barrier principles to protect the wall from the effect of rainfall infiltration. Singapore requires construction materials that are cost-effective to support sustainable urban development. Therefore, recycled materials are utilized as GBS materials to avoid the use of high-cost materials, such as steel or concrete. GBS consists of planting geobags with unique geosynthetic pockets for sustainable plant growth as a facing layer of GBS. The negative pore-water pressure (suction) within the reinforced soil behind GBS was assured to be constant during rainfall since GBS is designed specially to minimize the rainfall infiltration into the reinforced soil. This paper presents the practical design and stability analysis of the GBS, considering the presence of suction within the reinforced soil body. The monitoring of GBS performance in the field was carried out via field instrumentation. Finite element analyses of the GBS under extreme rainfalls were also performed for evaluation of the GBS performance. The field instrumentations and numerical analysis results showed that GBS was able to protect the slope from rainfall infiltration; therefore, the stability of the slope retained by GBS was not affected by the rainfall. Results from the analytical calculation showed that the most critical mode of failure is sliding along the base, followed by the global and local slope stability. The GBS is not susceptible to local instability.